Analisis Kelayakan Finansial Pengembangan Kelapa Kopyor di Kabupaten Pati - Faiq Yusron; Mukson; Siswanto Imam Santoso (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2025)
ENGLISH Kopyor coconut is an exotic Indonesian germplasm with high economic value. The largest coconut-producing region is Central Java Province, specifically Pati Regency. The potential for development remains significant due to the abundant availability of land. Despite its high value, the supply of kopyor coconut trees is still limited, so this condition results in the selling prices remaining relatively high. This study was conducted to evaluate the financial feasibility of the kopyor coconut agribusiness using payback period, Net B/C, NPV, and IRR analysis. The study was conducted from December 2023 to March 2024, involving 96 respondents from three sub-districts. The study results indicate that early maturing (genjah) kopyor coconut farming in Pati Regency is feasible, with a payback period of 4 years and 7 months. The Gross B/C values of 1.25 and Net B/C 1.91 are more than one or less than the economic life. NPV is positive at Rp219,613,433 at an interest rate (discount rate) of 12.00% per year with an Internal rate of return (IRR) of 31.96% which is greater than the prevailing bank interest of 12% per year. The cultivation of early maturing kopyor coconut in Pati Regency is feasible, and its development has the potential to generate optimal and sustainable profits for farmers. INDONESIA Kelapa kopyor merupakan plasma nutfah eksotik asli Indonesia yang memiliki nilai ekonomi tinggi. Daerah penghasil terbanyak berada di Provinsi Jawa Tengah, tepatnya di Kabupaten Pati. Potensi pengembangan masih terbuka lebar karena ketersediaan lahan cukup luas. Meskipun bernilai tinggi, ketersediaan tanaman kelapa kopyor masih terbatas sehingga harga jualnya relatif mahal. Penelitian ini dilakukan untuk mengevaluasi kelayakan finansial agribisnis kelapa kopyor dengan analisis payback period, Net B/C, NPV, dan IRR. Penelitian dilaksanakan pada Desember 2023 hingga Maret 2024 dengan jumlah sampel 96 dari tiga kecamatan. Hasil penelitian menunjukkan bahwa usaha tani kelapa kopyor genjah di Kabupaten Pati layak diusahakan. Payback period tercapai dalam 4 tahun 7 bulan. Nilai Gross B/C 1,25 dan Net B/C 1,91, keduanya lebih besar dari satu. NPV positif sebesar Rp219.613.433 menandakan present value melebihi biaya yang dikeluarkan. Tingkat suku bunga (discount rate) 12% menghasilkan IRR 31,96%, lebih besar dari bunga bank 12% per tahun. Usahatani kelapa kopyor genjah di Kabupaten Pati layak dilaksanakan dan pengembangannya berpotensi memberikan keuntungan optimal dan berkelanjutan bagi petani.